Chemical Evaluation of the Nutritive Quality of Pigeon Pea [Cajanus cajan (L.) Millsp.] - Akand, K.E.; Abubakar, M.M.; Adegbola, T.A.; Bogoro, S.E.; Doma, U.D. (International Journal of Poultry Science, 2009)
This study was carried out to evaluate the proximate and amino acid compositions of samples of raw and roasted pigeon pea seeds. The following range of values were obtained for dry matter (95.89-96.34%), crude protein (21.03-21.07%), crude fat (4.43-5.96%), crude fibre (7.16-7.52%) and ash (3.76-4.02%) respectively for the raw and roasted seeds of pigeon pea. While values for nitrogen free extract ranged from 57.77-59.51% for the roasted and raw pigeon pea seeds respectively. Results from the amino acid analysis revealed that some amino acids like arginine, aspartic acid, threonine, serine, glutamic acid, glycine, alanine, leucine and tyrosine had their concentration in the seeds increased with heat processing, while other amino acids were not. On the whole, the concentration of glutamic acid was found to be the highest in the pigeon pea, with a value of 14.21 g/16 gN for the roasted seeds. Lysine showed the highest concentration among the indispensable amino acids (7.79 g/16 gN for the raw seeds and 7.55 g/16 gN for the roasted seeds). Pigeon pea seed was found to be deficient in the sulphur-containing amino acids (cystine and methionine).